Crossed - Condie, Ally (New York Speak, 2013)
Chasing down an uncertain future, Cassia makes her way to the Outer Provinces in pursuit of Ky-taken by the Society to his certain death-only to find that he has escaped into the majestic, but treacherous, canyons. On this wild frontier are glimmers of a different life and the enthralling promise of rebellion. But even as Cassia sacrifices everything to reunite with Ky, ingenious surprises from Xander may change the game once again
1 14
NEW, LITERATURE
Keywords: Government, Resistance to -- Juvenile fiction; Insurgency -- Juvenile fiction; Mate selection -- Juvenile fiction; Self-realization -- Juvenile fiction